Procedure and private international law - Perdue, Wendy Collins, 1953- (Private international law ;, 2017)
This research review examines leading English language journal articles in the area of private international law. It focuses on a range of procedural issues that have particular salience for international litigation including the location of process and discovery, class actions and the aggregation of class, and the professional responsibility challenges of lawyers practicing in multiple jurisdictions. It provides valuable context and insight for the issues addressed. This research review is an essential tool for university and academic institution libraries and International law scholars.